Load monitoring in sports and its application in the field of winter sports - Haller, N.; Stöggl, T. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Athlete monitoring aims to maximize performance and prevent illness and injury. In winter sports, it is important for coaches to regularly monitor the training and competition load and the physiological response (i.e., internal load) 1,2, as well as athlete characteristics such as age, fitness, and injury history, as these have been identified as risk factors for injury 3,4. Here, we outline general principles of load monitoring and present current strategies and upcoming tools for athlete monitoring in winter sports.